2004
DOI: 10.1111/j.1470-6431.2004.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

The dietary and health behaviour of young people aged 18–25 years living independently or in the family home in Liverpool, UK

Abstract: An individual's dietary habits are largely developed during childhood and adolescence, and are likely to be determined by both nature (the development of sensory perceptions) and nurture (parental influence, and later on the influence of peers). However, diet is likely to evolve throughout the life cycle as circumstances change and new influences are introduced to an individual's lifestyle. An example of this is the changes in diet that occur as a result of the transition young people make away from the family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 13 publications
(11 reference statements)
4
46
1
Order By: Relevance
“…Similar results were found in a study on university students where 69% of them were not consuming the recommended fruit and vegetable intake (Huang et al, 2003). However, a study conducted one year later showed that students, who lived independently, away from home, had a healthier eating behaviour than the students living with their parents (Beasley et al, 2004).…”
Section: The Transitional Period and Risk Of Gain Weightsupporting
confidence: 80%
“…Similar results were found in a study on university students where 69% of them were not consuming the recommended fruit and vegetable intake (Huang et al, 2003). However, a study conducted one year later showed that students, who lived independently, away from home, had a healthier eating behaviour than the students living with their parents (Beasley et al, 2004).…”
Section: The Transitional Period and Risk Of Gain Weightsupporting
confidence: 80%
“…Other studies analyse the relationship between the food habits of young people and their lifestyles, especially in the passage from the family home to independent living (Beasley, Hackett, & Maxwell, 2004;Papadaki, Hondros, Scott, & Kapsokefalou, 2007;Riddell, Ang, Keast, & Hunter, 2011;Satalic, Baric, & Keser, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Germans with a Hauptschulabschluss (those who finish school after 9th grade, with no further education) are twice as likely to be overweight or obese than Germans with an Abitur (general qualification for university entrance; finishing school after 13th grade) or Fachhochschulreife (finishing school after 12th grade, no general qualification for university entrance) (Brombach et al, 2006). A study by Beasley et al (2004) find that respondents living independently are more likely to consume a "good" diet than those living in the family home (Beasley et al, 2004). Independent living may bring-on the responsibility of various food-related activities such as budgeting, purchase, preparation and cooking, which are skills that young adults may not possess when transitioning from a dependent living arrangement (Beasley et al, 2004;Crossley and Nazir, 2002).…”
Section: Obesity Residence and Food Choicementioning
confidence: 96%